Effect of Diameter Classes and Harvesting Intervals on Seed Bio-chemicals of Acer oblongum wall - Chauhan, K. C.; Kumar, A. N. Arun (Indian Forester, 2002)
Seeds collected from four different classes (D1=<20.50 cm; D2=20.51-30.50 cm; D3= 30.51- 40.50 cm and D4 =>40.51 cm) at six harvesting dates (Viz; C1 = 30th Dec., C2 = 15th Jan., C3 = 30th Jan., C4 = 15th. Feb., C5 = 1st March and C6 = 15th March) gave significant differences for different bio-chemical constituents viz; total, reducing, non-reducing sugars, total phenols, starch, total amino acids and soluble proteins. The combinations ofD1C6, D2C6, D3C6, and D4C6 registered the highest total and non-reducing sugars in their respective diameter classes. Whereas, harvesting date C3 (30th Jan.) in all diameter classes recorded maximum content of starch, total phenols, soluble proteins and total amino acids. The present study suggested that C3 (30th Jan.) was the best harvesting date irrespective of diameter classes in this species.